Penerapan Alat Kerja Check Sheet Terhadap Pengendalian Kualitas Usaha Kebun Anggrek Bu Uli - Rahmawati, Elly; Rairani Rahmasalma Dewi; Nadia Shafa Kamilah; Ahmad Ali Husen; Ronaldi Hasibuan (CV. Ulil Albab Corp, 2025)
Product quality plays a vital role in building customer trust and satisfaction, including in the operations of Kebun Anggrek Bu Uli. This study aims to analyze the implementation of the check sheet as a quality control tool at Kebun Anggrek Bu Uli in Bogor. The method used involved direct observation and systematic documentation, with the check sheet serving as the main instrument to collect data on the types and frequency of product defects. The analysis showed that the most frequent damage occurred in the roots and growing media, followed by damage to leaves and stems. The implementation of the check sheet proved effective in identifying the sources of quality issues and served as a basis for making improvement decisions. These results indicate that the check sheet is a simple yet strategic tool for supporting quality enhancement and improving customer satisfaction at Kebun Anggrek Bu Uli.